Targeting cuproptosis with nano material: new way to enhancing the efficacy of immunotherapy in colorectal cancer - Liu, Xiangdong; Zhang, Wanqiu; Wei, Shaozhong; Liang, Xinjun; Luo, Bo (Frontiers in Pharmacology, 2024)
Colorectal cancer has emerged as one of the predominant malignant tumors globally. Immunotherapy, as a novel therapeutic methodology, has opened up new possibilities for colorectal cancer patients. However, its actual clinical efficacy requires further enhancement. Copper, as an exceptionally crucial trace element, can influence various signaling pathways, gene expression, and biological metabolic processes in cells, thus playing a critical role in the pathogenesis of colorectal cancer. Recent studies have revealed that cuproptosis, a novel mode of cell death, holds promise to become a potential target to overcome resistance to colorectal cancer immunotherapy. This shows substantial potential in the combination treatment of colorectal cancer. Conveying copper into tumor cells via a nano-drug delivery system to induce cuproptosis of colorectal cancer cells could offer a potential strategy for eliminating drug-resistant colorectal cancer cells and vastly improving the efficacy of immunotherapy while ultimately destroy colorectal tumors. Moreover, combining the cuproptosis induction strategy with other anti-tumor approaches such as photothermal therapy, photodynamic therapy, and chemodynamic therapy could further enhance its therapeutic effect. This review aims to illuminate the practical significance of cuproptosis and cuproptosis-inducing nano-drugs in colorectal cancer immunotherapy, and scrutinize the current challenges and limitations of this methodology, thereby providing innovative thoughts and references for the advancement of cuproptosis-based colorectal cancer immunotherapy strategies.